Comparing knowledge, attitude and practice around meat safety in three developing countries (Nigeria, India, Vietnam) - Grace, Delia; Lapar, Ma. Lucila; Okike, Iheanacho; Varijakshapanicker, Padmakumar; Fahrion, Anna S. (2011)
Livestock consumption is rapidly increasing in poor countries, but as value chains evolve from rural to urban and from short to long food safety may deteriorate. Given the lack of adequate testing and inspection, it is important to understand the factors that influence choices made by meat value chain actors. We describe three related studies of knowledge, attitude and practice (KAP) of meat value chain actors in three very different countries. The studies involved mapping value chains followed by participatory appraisal, and administering questionnaires and check-lists to pork slaughterers, retailers and consumers in Nigeria, India and Vietnam (n = 403, n = 198, n = 246 respectively) and collecting meat samples for laboratory analysis. The study revealed interesting similarities and differences. In all countries, practices and knowledge were most problematic at the abattoir and least in the household. In Vietnam, concern over meat safety was high but self-reported gastrointestinal disease was low: the situation was reversed in India and Nigeria. Retailer knowledge and practices were better in meat sold in shops compared to those sold though traditional outlets; however, only in Nigeria was meat safer. Participatory methods revealed risky practices: retailers in Nigeria often taste raw meat in order to convince consumers it is safe; consumers in Nagaland keep pork in the chimney (a traditional preservation method of unknown efficacy). KAP studies can help understand behavior that influences food safety and hence development of messages and interventions that are appropriate and motivating.